A method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel
Through laser impact strengthening and hot and cold cycle processing, the surface nitriding channel of austenitic stainless steel is increased and ionic nitriding is performed at low temperatures, which solves the problem of high brittleness of the nitride layer, achieves coordinated control of high hardness and low brittleness, and improves the wear and corrosion resistance of stainless steel.
Patent Information
- Application Number
- CN202211706605.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-29
AI Technical Summary
After the low-temperature nitriding treatment, the nitride layer has a high brittleness, resulting in a decrease in wear resistance and affecting its application.
Laser impact-enhancing pretreatment and hot and cold cycle treatment are used to form micro-nano crystals, increase nitriding channels, and ionic nitriding treatment is carried out at 400-450°C to reduce nitride aggregation on the surface.
Effectively reduce the surface brittleness of the nitriding layer, improve the surface hardness and wear resistance of austenitic stainless steel, enhance its corrosion resistance, and meet the requirements of long-term service in industrial production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel, belonging to the technical field of metal material surface modification. Background Art
[0002] Austenitic stainless steel has excellent corrosion resistance and is widely used in many fields, but its poor hardness and wear resistance limit the application of austenitic stainless steel. Ion nitriding is the process of infiltrating nitrogen atoms into the surface of stainless steel to form nitrides with higher hardness, which can enhance the surface hardness and wear resistance of stainless steel. By ion nitriding austenitic stainless steel at low temperature (T<450℃), a nitrogen-rich supersaturated austenite nitride layer (S phase) can be obtained. Under the appropriate time of ion nitriding, the precipitation of chromium nitride can be effectively inhibited to avoid the corrosion resistance of austenitic stainless steel. Under low temperature conditions, the diffusion power of nitrogen is small and it mainly diffuses along the grain boundaries. Since there are generally fewer grain boundary channels on the surface of austenitic stainless steel, a large number of nitrides will gather at the grain boundaries, making the nitride layer brittle, resulting in a decrease in the wear resistance of austenitic stainless steel, which seriously affects the application of low-temperature nitrided austenitic stainless steel. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned defects and provide a method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel, thereby solving the technical problem of high brittleness of the nitrided layer of existing low-temperature nitrided austenitic stainless steel. The present invention can effectively reduce the surface brittleness of the nitrided layer.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] A method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel, comprising:
[0006] S1 cleans and dries the surface of austenitic stainless steel;
[0007] S2 performs laser strengthening pretreatment on the surface of austenitic stainless steel;
[0008] S3 performs hot and cold cycle treatment on austenitic stainless steel;
[0009] S4 is an ion nitriding treatment for austenitic stainless steel.
[0010] Furthermore, in step S1, the surface of the austenitic stainless steel is cleaned in sequence using acetone, alcohol and deionized water;
[0011] Acetone, alcohol and deionized water are industrial grade with purity greater than 99%.
[0012] Furthermore, in step S2, laser shock strengthening equipment is used to perform laser strengthening pretreatment on the surface of the austenitic stainless steel.
[0013] Furthermore, in step S2, the process parameters for laser strengthening pretreatment of the surface of austenitic stainless steel using laser shock strengthening equipment are:
[0014] The laser spot diameter is 2~3mm, the number of impacts is 3~5 times, the repetition frequency is 10~20Hz, the pulse width is 18ns, the laser wavelength is 1064nm, and the power is 6.5J.
[0015] Furthermore, in step S2, the thickness of the laser strengthening pretreatment layer is 300-500 microns.
[0016] Further, in step S3, the austenitic stainless steel is subjected to 10-15 times of hot and cold cycle treatment;
[0017] When austenitic stainless steel is subjected to hot and cold cycle treatment, the high temperature is 100°C, the low temperature is liquid nitrogen, and the holding time is 10 to 15 minutes.
[0018] Furthermore, in step S4, the austenitic stainless steel is ion nitrided at 400-450°C.
[0019] Furthermore, in step S4, the method for performing ion nitriding treatment on austenitic stainless steel is:
[0020] S4.1 Place the austenitic stainless steel into the nitriding furnace, evacuate to 10-20Pa, adjust the working voltage to 700-800V, and the duty cycle to 70%-80%;
[0021] S4.2 conveying ammonia and hydrogen, wherein the flow ratio of ammonia to hydrogen is 3:1-2:1;
[0022] S4.3 Adjust the gas flow rate to maintain the gas pressure of the nitriding furnace at 90~110Pa;
[0023] S4.4 Control the temperature of the nitriding furnace to 400-450℃ and nitriding for 8-12h.
[0024] Furthermore, in step S2, when laser strengthening pretreatment is performed on the surface of austenitic stainless steel using laser shock strengthening equipment, the laser shock strengthening equipment is a nanosecond Gaia type laser shock strengthening equipment.
[0025] Furthermore, in step S2, when laser strengthening pretreatment is performed on the surface of austenitic stainless steel using laser shock strengthening equipment, the aluminum foil is used as an absorption layer and the liquid water is used as a constraint layer.
[0026] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0027] (1) The present invention proposes a method for synergistically controlling the high hardness and low brittleness of the surface layer of ultra-high strength stainless steel. The laser shock strengthening technology is used to refine the surface grains of austenitic stainless steel and increase the nitriding channels. The surface of austenitic stainless steel can be strengthened, the surface hardness and wear resistance of austenitic stainless steel can be increased, and the laser shock strengthening can remove the loose layer on the surface of austenitic stainless steel, which is beneficial to the improvement of the hardness and corrosion resistance of the workpiece.
[0028] (2) The present invention reduces the surface residual stress after laser shock strengthening and prevents cracks and deformation of the workpiece during the nitriding process by adding high and low temperature cold and hot cycles between laser shock strengthening and ion nitriding.
[0029] (3) During the nitriding process, the present invention can perform ion nitriding at low temperature and quickly due to the presence of numerous grain boundary channels on the surface, thereby effectively preventing nitrides from aggregating on the surface and reducing the surface brittleness of the nitrided layer.
[0030] (4) The low-temperature ion nitriding of the present invention does not generate chromium nitride, and compared with high-temperature nitriding, the corrosion resistance of the workpiece is significantly improved.
[0031] (5) The method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel of the present invention can solve the surface brittleness problem of austenitic stainless steel during low-temperature nitriding, and prepare complex austenitic stainless steel components that meet the long-term service requirements of industrial production.
[0032] (6) The surface hardness of the austenitic stainless steel produced by the present invention is ≥HV0.51000, the depth of the nitrided layer is 100-300 μm, and the brittleness of the nitrided layer is level 1. DETAILED DESCRIPTION
[0033] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0034] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0035] This paper proposes a method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel. This method uses laser shock strengthening technology to form micro-nano crystals on the surface of austenitic stainless steel by laser shock strengthening, increase the diffusion channel of ion nitriding nitrogen atoms, so that nitrogen atoms can quickly penetrate into the interior of austenitic stainless steel through micro-nano crystals at low temperatures, reduce the aggregation of nitrides on the surface grain boundaries, and reduce the brittleness of the surface nitride layer while obtaining high-hardness austenitic stainless steel on the surface. High hardness and low brittleness of the surface of austenitic stainless steel are achieved.
[0036] The method of the invention mainly comprises two stages: laser strengthening pretreatment and ion nitriding.
[0037] Laser strengthening pretreatment:
[0038] By using pulsed laser to impact strengthen the surface of austenitic stainless steel, micro-nano crystals are formed on the surface of austenitic stainless steel, the grains on the surface of austenitic stainless steel are refined, a large number of nitrogen atom diffusion channels are formed, and the surface of austenitic stainless steel is strengthened.
[0039] Ion nitriding:
[0040] Austenitic stainless steel is placed in an ion nitriding furnace and nitrided at a temperature of 400-450°C.
[0041] A method for synergistically controlling high hardness and low brittleness of the surface layer of ultra-high strength stainless steel, the specific steps are as follows:
[0042] (1) Use acetone, alcohol, and deionized water to clean the surface of austenitic stainless steel once, and then dry the surface.
[0043] (2) The dried austenitic stainless steel is placed in a laser shock peening device with a laser spot diameter of 3 mm, 3 shock times, a repetition frequency of 10 Hz, a pulse width of 18 ns, a laser wavelength of 1064 nm, and a power of 6.5 J to perform surface strengthening treatment on the surface of the austenitic stainless steel. Preferably, the laser pulse strengthening thickness is 300-500 microns.
[0044] (3) The austenitic stainless steel in (2) is subjected to 10-15 high and low temperature cold and hot cycle treatments.
[0045] (4) Place the austenitic stainless steel sample in (3) into a nitriding furnace, evacuate to 10-20 Pa, adjust the working voltage to 700-800 V, and the duty cycle to 70%-80%. Then deliver ammonia and hydrogen. The gas ratio is generally between 3:1-2:1. Adjust the flow rate so that the gas pressure is maintained at 100 Pa. The temperature is controlled at about 400-450°C. Nitriding is performed for 8-12 hours. When the temperature in the furnace is ≤100°C, the furnace is inflated and opened.
[0046] In step (1), the anhydrous ethanol, acetone and deionized water are all industrial grade with a purity greater than 99%.
[0047] In step (2), the laser is a nanosecond Gaia laser shock peening device. Preferably, aluminum foil is used as the absorption layer and liquid water is used as the confinement layer.
[0048] In step (3), the high temperature is 100°C, the low temperature is liquid nitrogen, and the holding time is 10 minutes.
[0049] Example 1
[0050] Acetone, alcohol, and deionized water were used to clean the surface of austenitic stainless steel once, and then the surface was dried. The dried austenitic stainless steel was placed in the laser shock strengthening equipment, with a laser spot diameter of 3mm, 3 shocks, a repetition frequency of 10Hz, a pulse width of 18ns, a laser wavelength of 1064nm, and a power of 6.5J to strengthen the surface of the austenitic stainless steel. The laser pulse strengthening thickness is about 421 microns. Then the austenitic stainless steel sample was subjected to 10 high and low temperature hot and cold cycle treatments. Then the austenitic stainless steel sample was placed in the nitriding furnace, evacuated to 10Pa, the working voltage was adjusted to 800V, the duty cycle was 70%, and then ammonia and hydrogen were delivered with a gas ratio of 2:1. The flow rate was adjusted so that the gas pressure was maintained at 100Pa and the temperature was controlled at about 450℃ for nitriding for 10h. The furnace was inflated and opened when the temperature in the furnace was ≤100℃. The surface hardness of the nitrided layer is HV 0.5 1421, the total infiltration layer thickness is about 200 microns.
[0051] Example 2
[0052] Acetone, alcohol, and deionized water were used to clean the surface of austenitic stainless steel once, and then the surface was dried. The dried austenitic stainless steel was placed in the laser shock strengthening equipment. The laser spot diameter was 3mm, the number of shocks was 2 times, the repetition frequency was 10Hz, the pulse width was 18ns, the laser wavelength was 1064nm, and the power was 6.5J to strengthen the surface of the austenitic stainless steel. The laser pulse strengthening thickness is about 358 microns. Then the austenitic stainless steel sample was subjected to 10 high and low temperature hot and cold cycle treatments. Then the austenitic stainless steel sample was placed in the nitriding furnace, evacuated to 10Pa, the working voltage was adjusted to 700V, the duty cycle was 70%, and then ammonia and hydrogen were delivered. The gas ratio was generally between 1:1, and the flow rate was adjusted so that the gas pressure was maintained at 100Pa. The temperature was controlled at about 450℃, and the nitriding was 10h. The furnace was inflated and opened when the temperature in the furnace was ≤100℃. The surface hardness of the nitrided layer is HV 0.5 1074, the total infiltration layer thickness is about 125 microns.
[0053] Example 3
[0054] Acetone, alcohol, and deionized water were used to clean the surface of austenitic stainless steel once, and then the surface was dried. The dried austenitic stainless steel was placed in the laser shock strengthening equipment. The laser spot diameter was 2mm, the number of shocks was 3 times, the repetition frequency was 20Hz, the pulse width was 18ns, the laser wavelength was 1064nm, and the power was 6.5J to strengthen the surface of the austenitic stainless steel. The laser pulse strengthening thickness is about 541 microns. Then the austenitic stainless steel sample was subjected to 10 high and low temperature hot and cold cycle treatments. Then the austenitic stainless steel sample was placed in the nitriding furnace, evacuated to 10Pa, the working voltage was adjusted to 800V, the duty cycle was 70%, and then ammonia and hydrogen were delivered. The gas ratio was generally between 2:1, and the flow rate was adjusted so that the gas pressure was maintained at 100Pa. The temperature was controlled at about 450℃, and the nitriding was 10h. The furnace was inflated and opened when the temperature in the furnace was ≤100℃. The surface hardness of the nitrided layer is HV 0.5 1537, the total penetration layer thickness is about 246 microns.
[0055] The properties of the products obtained in Examples 1 to 3 are shown in Table 1. The method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel of the present invention can solve the surface brittleness problem of low-temperature nitriding of austenitic stainless steel, and prepare complex austenitic stainless steel components that meet the long-term service requirements of industrial production.
[0056] Table 1 Performance of the products obtained in Examples 1 to 3
[0057]
[0058] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0059] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. A method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel, characterized in that: include: S1 cleans and dries the surface of austenitic stainless steel; S2 performs laser strengthening pretreatment on the surface of austenitic stainless steel; S3 performs hot and cold cycle treatment on austenitic stainless steel; S4 performs ion nitriding treatment on austenitic stainless steel; In step S2, the process parameters for laser strengthening pretreatment of the austenitic stainless steel surface using laser shock strengthening equipment are: The laser spot diameter is 2~3mm, the number of impacts is 3~5 times, the repetition frequency is 10~20Hz, the pulse width is 18ns, the laser wavelength is 1064nm, and the power is 6.5J; In step S2, the thickness of the laser strengthening pretreatment layer is 300-500 microns; In step S3, the austenitic stainless steel is subjected to 10-15 times of hot and cold cycle treatment; When austenitic stainless steel is subjected to hot and cold cycle treatment, the high temperature is 100°C, the low temperature is liquid nitrogen, and the holding time is 10 to 15 minutes; In step S4, the method for ion nitriding austenitic stainless steel is: S4.1 Place the austenitic stainless steel into the nitriding furnace, evacuate to 10-20Pa, adjust the working voltage to 700-800V, and the duty cycle to 70%-80%; S4.2 conveying ammonia and hydrogen, wherein the flow ratio of ammonia to hydrogen is 3:1-2:1; S4.3 Adjust the gas flow rate to maintain the gas pressure of the nitriding furnace at 90~110Pa; S4.4 Control the temperature of the nitriding furnace to 400-450℃ and nitriding for 8-12h.
2. The method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel according to claim 1, characterized in that: In step S1, the surface of the austenitic stainless steel is cleaned in sequence using acetone, alcohol and deionized water; Acetone, alcohol and deionized water are industrial grade with purity greater than 99%.
3. The method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel according to claim 1, characterized in that: In step S2, laser strengthening pretreatment is performed on the surface of austenitic stainless steel using laser shock strengthening equipment.
4. The method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel according to claim 1, characterized in that: In step S4, the austenitic stainless steel is ion nitrided at 400-450°C.
5. The method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel according to claim 3, characterized in that: In step S2, when laser strengthening pretreatment is performed on the surface of austenitic stainless steel by using laser shock peening equipment, the laser shock peening equipment is a nanosecond Gaia type laser shock peening equipment.
6. A method for coordinated control of high hardness and low brittleness of the surface layer of ultra-high strength stainless steel according to claim 5, characterized in that: In step S2, when laser strengthening pretreatment is performed on the surface of austenitic stainless steel using laser shock strengthening equipment, the aluminum foil is used as an absorption layer and the liquid water is used as a constraint layer.
Citation Information
Patent Citations
Laser shock technology for improving ion nitriding efficiency
CN108441625A